Tempat Sampah Pintar Berbasis IoT - Raemon Syaljumairi; Cipto Prabowo; Dwi Latiffah Hanum (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
The behavior of people who often litter is one of the factors that affect environmental cleanliness. For this reason, an innovative tool is needed, namely the Smart Trash Can that is able to manage waste using a water sensor and determine the capacity and distance of the waste object using an ultrasonic sensor and can perform automatic control of the type of waste using a servo output. This Smart Trash can make it easier for users to manage waste on a small scale. How this tool works uses NodeMCU as a microcontroller to retrieve data generated by rain sensors, ultrasonic sensors, and micro servos. Because NodeMCU already has a wifi module, the data is sent to telegram for garbage notification and communication between trash bins.